The THE ROLE OF EARLY CHILDHOOD EDUCATION TEACHERS IN PROVIDING EDUCATIONAL SERVICES FOR CHILDREN WITH SPECIAL NEEDS AT PKG PAUD MELONGUANE DISTRICT - Saroinsong, Nola Melda; Puridawaty, Brigita; Peloan, Dorneka; Singkana, Min; Bahasa, Reny (International Conferences on Early Childhood Education Proceedings, 2024)
ABSTRACT Teachers play a crucial role in helping develop the optimal abilities of learners. One of their current roles is to provide services needed by learners with special needs. Children with special needs are those experiencing developmental issues, requiring educational services that cater to their early childhood needs. Special education services for these children aim to maximize their potential from an early age. This research aims to explore the role of early childhood education (ECE) teachers in providing educational services for children with special needs. The research methodology used in this study was a survey method, and the findings indicate that the role of ECE teachers in providing educational services for children with special needs at PKG PAUD Melonguane is 22.38%, involving 15 out of 67 ECE teachers. Keywords: ECE Teacher Role, Educational Services, Children with Special Needs.